2018
DOI: 10.1103/physrevb.98.155316
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-mediated optomechanical forces in semiconductor nanomembranes with coupled quantum wells

Abstract: In the majority of optomechanical experiments, the interaction between light and mechanical motion is mediated by radiation pressure, which arises from momentum transfer of reflecting photons. This is an inherently weak interaction, and optically generated carriers in semiconductors have been predicted to be the mediator of different and potentially much stronger forces. Here we demonstrate optomechanical forces induced by electron-hole pairs in coupled quantum wells embedded into a free-free nanomembrane. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The coefficient of thermal expansion for the III-V semiconductors in low temperatures is minimal, which is opposite to the low-dimensional semiconductor systems. Hence, the photothermal effect in exciton optomechanical systems based on semiconductor quantum wells in low temperatures can be neglected, 101 while for the low-dimensional exciton optomechanical system, the photothermal effect could not be neglected. 45 Andreas Barg et al investigated carrier-mediated optomechanical forces in semiconductor nanomembranes with coupled quantum wells.…”
Section: Exciton-mediated Optomechanical Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The coefficient of thermal expansion for the III-V semiconductors in low temperatures is minimal, which is opposite to the low-dimensional semiconductor systems. Hence, the photothermal effect in exciton optomechanical systems based on semiconductor quantum wells in low temperatures can be neglected, 101 while for the low-dimensional exciton optomechanical system, the photothermal effect could not be neglected. 45 Andreas Barg et al investigated carrier-mediated optomechanical forces in semiconductor nanomembranes with coupled quantum wells.…”
Section: Exciton-mediated Optomechanical Forcesmentioning
confidence: 99%
“…45 Andreas Barg et al investigated carrier-mediated optomechanical forces in semiconductor nanomembranes with coupled quantum wells. 101 The free-free nanomembranes with embedded CQWs are shown in Fig. 6(a and b).…”
Section: Exciton-mediated Optomechanical Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Barg et al have recently revealed how the exciton relaxation affects the optical drive efficiency of mechanical motion and experimentally showed how to optimize it with an external electric field [15]. However, its counter process, how mechanical motion affects the exciton relaxation process, has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In direct-bandgap semiconductors, photoelastic effects typically dominate optomechanical coupling [27] and are greatly enhanced near electronic resonances of the material [28]. Moreover, in micromechanical resonators hosting quantum wells (QWs), electronic transitions can be tailored to boost carrier-mediated mechanical effects [29]. In both cases, an increase of optical absorption affects the cavity finesse and favors photothermal effects, while mechanical dephasing can be activated through photogenerated carriers [30,31].…”
mentioning
confidence: 99%